1981
DOI: 10.1007/bf00825066
|View full text |Cite
|
Sign up to set email alerts
|

Droplet breakup regimes and criteria for their existence

Abstract: An analysis of experimental and theoretical studies of droplet breakup by a gas flow in shock tubes and nozzles is presented.A system of criteria defining droplet breakup regimes is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The secondary break‐up was not considered due to the low Weber number of the droplets 24 (maximum of 1.5). The effects of Brownian motion were also not included.…”
Section: Methodsmentioning
confidence: 99%
“…The secondary break‐up was not considered due to the low Weber number of the droplets 24 (maximum of 1.5). The effects of Brownian motion were also not included.…”
Section: Methodsmentioning
confidence: 99%
“…In Adiga et al, 11 it was shown that these shock wave blast-impacted bigger droplets produced a cloud of fine mist due to the shock energy absorption owing to the discontinuity in the thermophysical properties across the normal shock (Chauvin et al 12 ). The mist region (Borisov et al 13 ) exhibits significantly small new droplets formed from the parent droplet at very high relative velocities where “secondary” droplet disintegration is associated with many droplet breakup modes providing variation in drop size distribution (Gelfand et al 14 ).…”
Section: Introductionmentioning
confidence: 99%